The FMEA AND ITS ROLE IN PROCESS IMPROVEMENT: Preposition for applying the tool in a company in the food sector - de Lima Oliveira, Graziele; José Casagrande , Diego (Revista Interface Tecnológica, 2024)
Failure Mode and Effects Analysis (FMEA) is a systematic methodology used in maintenance planning and control to recognize, evaluate and mitigate risks related to products, processes or systems. One of the first forms of failure analysis was developed by the United States Air Force during World War II, with FMEA being formalized and initially documented in the military standard MIL-P-1629 in 1949. Over the years, the method was improved . The objective of this article is to propose the application of Failure Modes and Effects Analysis (FMEA) tools in the maintenance area of ​​companies in the food sector in order to identify, prioritize and optimize the performance of their processes. The approach adopted in this investigation involved a thorough literature review, investigation of the historical origins of this technique, its use in specific sectors and innovative tactics for improvement. The study revealed that the adoption of FMEA in the industry brought a considerable improvement in quality management and product safety. Providing early detection of potential failures and their impacts, allowing the implementation of more effective corrective and preventive actions. As a result, the company saw a decrease in non-compliance incidents and an increase in customer satisfaction.
Keywords: FMEA; Maintenance; Process improvement